Case report: Successful treatment with biologics in a pediatric patient with a severe inflammatory skin disease and novel CARD14 mutation - Niedźwiedź, Michał; Narbutt, Joanna; Siekierko, Aleksandra; Skibińska, Małgorzata; Kwiek, Bartłomiej; Sobolewska-Sztychny, Dorota; Ciążyńska, Magdalena; Poznańska-Kurowska, Katarzyna; Gostyński, Antoni; Lesiak, Aleksandra (Frontiers in Medicine, 2024)
CARD14 (caspase activation and recruitment domain) mutations have been associated with psoriasis vulgaris, psoriatic arthritis, generalized and palmoplantar pustular psoriasis, pityriasis rubra pilaris, and atopic dermatitis. We present a pediatric patient with a novel CARD14: c.394A > T/− (Ile123Phe) mutation, diagnosed with CARD14-associated papulosquamous eruption (CAPE), who was successfully treated with biological treatment.